DAMPAK KOMITMEN DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN TAPANULI TENGAH - Ayu Handari; Rahmadiah Hanum; Zafril Abdi Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research seeks answers to the impact of commitment and individual characteristics on employee performance at the DPRD Secretariat of Central Tapanuli Regency. Using a sample of 35 employees, Multiple Linear Regression analysis was carried out. The results of the t test show that commitment (X1) has a positive and significant effect on employee performance (Y), with tcount of 2.551 > ttable 2.034, and Sig 0.016 < 0.05. On the other hand, individual characteristics (X2) do not have a significant effect on employee performance, with tcount 2.092 < ttable 2.034, and Sig 0.044 > 0.05. The F test states that simultaneously, commitment and individual characteristics have a positive and significant effect on employee performance (Fcount 7.151 > Ftable 3.29). The research conclusion confirms that individual commitment and characteristics have a positive and significant effect on employee performance at the DPRD Secretariat of Central Tapanuli Regency. Thus, the hypothesis of this research can be accepted, indicating that these factors partially or simultaneously influence employee performance.